(untitled) (Al-Mansour Journal, 2023)
A systolic pressure has a top (systolic) and bottom (pulse pressure) number (diastolic) Normal. People who already have hypertension that is greater than average should ask their doctor about how to lower it. Previously, the level was set at 140/90 mm Hg for people below the age of 65and 150/80 mm Hg for those 65 and older. The purpose of this research is to establish the reference range of red blood cells hydroxylated (Hb A1c percent) within the (males and females) and to forecast Bp blood pressure diastolic. This means 70% to 79% of age 65- and 150/80-mm Hg for those ages 65 and older Diastolic blood pressure systolic. In this paper sampling is taken from 100andbased on data mining model, which is substitute for the decision tree calculative algorithm which one of one of the fields Artificial intelligent which analysis of appropriate decision-making can be used to visually represent decisions and processes operations prospecting.